Identificación y caracterización de pasivos ambientales mineros en la microcuenca de la quebrada Hierro de la parroquia San Carlos de las Minas, cantón Zamora y provincia de Zamora Chinchipe - Quezada Ponce, Ana Gabriela (2020)
The Nambija River is the main tributary of the San Carlos de las Minas parish, which in turn is made up of several micro-basins, one of them the micro-basin of the Hierro ravine with an area of 21.40 km2, in which its current situation through the description of the baseline, as well as the identification, characterization, evaluation and proposal of measures for the remediation of Mining Environmental Liabilities. The study area is characterized by having a humid subtropical climate and high rainfall even in the driest months, the temperature varies from 18 to 24°C and its rainfall from 1582.77 to 1641.68 mm / year. Air quality is good despite the development of mining and agricultural activities. Geologically, there is a sedimentary volcano sequence that houses the gold mineralization’s forming a band of a few kilometers within a batolith of granodioritic composition, the Piuntza, Saquea and Zamora Intrusive Complex units emerge, rocks such as: granite, granodiorite, andesite’s, basaltic andesite’s, andesitic tuffs and rhyolites. The Water Quality Index indicates that in the upper part of the microbasin the water is of good quality, while in the middle and lower part the water is regularly contaminated due to the development of mining and agricultural activities. The kind of slopes that predominate are very steeply inclined with values that range between 30 and 45o, this being a risk factor for landslides to occur. The type of soil present is of the inceptisol order, characterized by poorly defined profiles and its high organic matter content typical of the Amazon region. The landscape is favorable for the presence of bodies of water such as waterfalls and streams, mountainous reliefs with abundant flora and fauna. The predominant vegetation cover is the native boque with a percentage of 84.78% of the total area. Regarding the flora, three strata were identified: herbaceous, shrubby and arboreal; predominantly ferns, milkweed, guarumo, cedar and rosemary. Due to the location of the San Carlos de las Minas parish at the transition site of the Andes and the Amazon, the richness of fauna is significant, with the greater presence of birds. The area of direct influence of the study area is the Los Laureles neighborhood, located 8 km from the parish head, through surveys it was determined that the neighborhood has 39 inhabitants distributed as follows: 23 adults, 5 adolescents and 11 children The environmental sensitivity of the study area varies from high, medium and low depending on the factor affected. Field trips identified the presence of 14 mining environmental liabilities, belonging to 4 concessions: El Inicio, Playas de Sultana 7, Nanguipa and Sultana Unificada. Each of them was subsequently characterized and evaluated by the matrix of Vicente Conesa Fernandez (1997); resulting in 8 PAMs of low importance that correspond to waste such as trucks, polymers, a concrete, metal tubes; these in few quantities. 3 PAMs of medium importance being these metallic residues in large quantities and 3 PAMs of high importance, one of them being on the water resource and a mine mouth with the presence of acidic rock drainage. Measures were specified for the mitigation, control and / or remediation of environmental alterations generated by the presence of PAMs, with the aim of ensuring the sustainable use of the natural resources involved and the protection of the environment. The tentative budget for the mitigation, remediation and / or correction of these 14 PAMs is USD 4510.00.